MODEL MASSAGE EFFLEURAGE, PIJAT OKSITOSIN SENAM NIFAS MEMPERCEPAT INVOLUSI UTERUS PADA IBU POST PARTUM - Kasiati Kasiati; Ni Wayan Dwi Rosmalawati (Poltekkes Kemenkes Malang, 2019)
Post partum hemorrhage, one of the causes is weak uterine contraction or atonia, this may cause subinvolution, placental retention, infection and hamorrhage or HPP. Attempts to mediate by improving contraction, retraction and strong myometrous through massage effleurage or stimulating the release of oxytocin hormone by means of oxytocin massage and puerperal exercises are an important part of postpartum care. The purpose of this study proves the effect of massage effleurage model, massage of oxytocin and puerperal gymnastics on uterine uterine invitation of post partum mother at BPM Clinic of Lawang District. The research method is Quasy Experiment with Post Randomized Control Group Only Test Group. Population and sample in this research is post partum mother, with sample size 20 respondent, while sampling technique with Consecutive Rondom Sampling. The research instrument used questionnaire and observation sheet. The results of the uterine involution study were faster in all post partum mothers who performed massage effleurage and oxytocin massage, whereas in the postpartum gymnastics group almost all respondents, this is more than the group that did not intervene showed that the slow uterine involution most of the respondents. Tests of variables with Mann Whitney Test value of p is smaller than 0.05. That group of massage effleurage, massage of oxytocin p value 0.005 and pediatric gymnastic group p value 0.011, means there is effect of massage effleurage model, and postnatal gymnastics on the acceleration of involution in post mothersModels of massage effleurage, massage of oxytocin and gymnastics are non pharmacological therapy recommended some independent nursing intervention, does not require cost and side effects if done correctly on post partum mother to accelerate involution of the uterus so as to mediate bleeding and puerperal infections.